2015
DOI: 10.1111/pai.12296
|View full text |Cite
|
Sign up to set email alerts
|

Optimal duration of allergen immunotherapy in children with dust mite respiratory allergy

Abstract: Three years of SCIT induced significant improvement in children with dust mite respiratory allergy, but a 5-yr course added clinical improvement in rhinitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 27 publications
(47 reference statements)
0
22
0
3
Order By: Relevance
“…Additional data analyses stratified by study completion status (not shown in the paper) revealed, that the number of patients lost to follow‐up after the first year was independent of the treatment outcome: Patients documented for only 12 months showed the same 12 months efficacy and tolerability (vs. baseline) as patients completing the full 24 month study course. However, from this finding it cannot be concluded that AIT can be generally terminated after one year of treatment since additional and long‐lasting benefits of a longer treatment period may be expected .…”
Section: Discussionmentioning
confidence: 88%
“…Additional data analyses stratified by study completion status (not shown in the paper) revealed, that the number of patients lost to follow‐up after the first year was independent of the treatment outcome: Patients documented for only 12 months showed the same 12 months efficacy and tolerability (vs. baseline) as patients completing the full 24 month study course. However, from this finding it cannot be concluded that AIT can be generally terminated after one year of treatment since additional and long‐lasting benefits of a longer treatment period may be expected .…”
Section: Discussionmentioning
confidence: 88%
“…178 Similarly, children randomized to 3 or 5 years HDM SCIT had similar outcomes at 5 years. 179 So, in summary, for patients with AR, a minimum of 3 years of AIT is recommended to achieve long-term efficacy after treatment discontinuation (Grade A) ( Table 7).…”
Section: How Long Ait Sh Ould Be Contin Ued For In Ar?mentioning
confidence: 99%
“…Both treatment durations produced excellent results in terms of asthma remission (50% at 3 years and 54% at 5 years); these rates of asthma remission were significantly higher when compared with those detected in the control group (3.3%). A specific analysis that evaluated the clinical efficacy of 3 vs. 5 year of SCIT in children with HDM respiratory allergy demonstrated that 3 years of SCIT induces significant improvement in children with dust mite respiratory allergy, but a 5-year course added clinical improvement in rhinitis [142].…”
Section: Pediatric Populationsmentioning
confidence: 99%